Organizadores textuais e plano de texto: a forma e - Rosa, Rute; Fidalgo, Marta; Gonçalves, Matilde; Leal, Audria; Jorge, Noémia (Revista da Associação Portuguesa de Linguística, 2018)
Situated within the theoretical framework of Sociodiscursive Interactionism, this paper focuses on the role of textual organisers as elements that contribute to the identification of the text plan. The notion of textual organisers has been addressed by various authors and there are still several terminological variations and different categorisation proposals. Based on a qualitative textual analysis, this article discusses the functioning of the form and (e in Portuguese), in order to demonstrate that the functions of textual organisers are constituted on the textual level and that their categorisation has fluid boundaries.